Next-Generation Sequencing Approach in Methylation Analysis of HNF1B and GATA4 Genes: Searching for Biomarkers in Ovarian Cancer - Bubancova, Ivana; Kovarikova, Helena; Laco, Jan; Ruszova, Ema; Dvorak, Ondrej; Palicka, Vladimir; Chmelarova, Marcela (International journal of molecular sciences, 2017)
DNA methylation is well-known to be associated with ovarian cancer (OC) and has great potential to serve as a biomarker in monitoring response to therapy and for disease screening. The purpose of this study was to investigate methylation of HNF1B and GATA4 and correlate detected methylation with clinicopathological characteristic of OC patients. The study group consisted of 64 patients with OC and 35 control patients. To determine the most important sites of HNF1B and GATA4, we used next-generation sequencing. For further confirmation of detected methylation of selected regions, we used high-resolution melting analysis and methylation-specific real-time polymerase chain reaction (PCR). Selected regions of HNF1B and GATA4 were completely methylation free in all control samples, whereas methylation-positive pattern was observed in 32.8% (HNF1B) and 45.3% (GATA4) of OC samples. Evaluating both genes together, we were able to detect methylation in 65.6% of OC patients. We observed a statistically significant difference in HNF1B methylation between samples with different stages of OC. We also detected subtype specific methylation in GATA4 and a decrease of methylation in late stages of OC. The combination of unmethylated HNF1B and methylated GATA4 was associated with longer overall survival. In our study, we employed innovative approach of methylation analysis of HNF1B and GATA4 to search for possible epigenetic biomarkers. We confirmed the significance of the HNF1B and GATA4 hypermethylation with emphasis on the need of selecting the most relevant sites for analysis. We suggest selected CpGs to be further examined as a potential positive prognostic factor.
Keywords: regulace genové exprese u nádorů; dospělí; Kaplan-Meier Estimate; nádory vaječníků; Female; Adult; ženské pohlaví; Kaplanův-Meierův odhad; High-Throughput Nucleotide Sequencing; Gene Expression Regulation, Neoplastic; lidé; staging nádorů; Neoplasm Grading; Ovarian Neoplasms; GATA4 Transcription Factor; následné studie; metylace DNA; hepatocytární jaderný faktor 1-beta; prognóza; stupeň nádoru; Follow-Up Studies; nádorové biomarkery; Aged; vysoce účinné nukleotidové sekvenování; DNA Methylation; Hepatocyte Nuclear Factor 1-beta; Prognosis; Biomarkers, Tumor; lidé středního věku; senioři; promotorové oblasti (genetika); Promoter Regions, Genetic; Middle Aged; Neoplasm Staging; transkripční faktor GATA4; Humans